2008
DOI: 10.1002/eji.200737661
|View full text |Cite
|
Sign up to set email alerts
|

A heat shock protein gene (Hsp70.1) is critically involved in the generation of the immune response to myelin antigen

Abstract: Protracted inflammation has been associated with the generation of autoimmune responses. In this respect, increase in the chaperonin, heat shock protein 70 (hsp70) is an outcome of prolonged inflammatory stress. Previous experiments have shown that overexpression of inducible hsp70 in vitro enhanced myelin autoantigen recognition. To prove the role of hsp70 in myelin-directed responses in vivo, we applied a mouse deficient in the major gene encoding inducible hsp70, hsp70.1. Hsp70.1 -/-mice sensitized for expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 62 publications
5
27
0
Order By: Relevance
“…A significant upregulation of Hsp70 expression has been detected in CNS lesions from MS patients (63,64,68 (103). These data suggest that Hsp70 upregulation may increase susceptibility to autoimmune demyelinating disease.…”
Section: Cellular Responsementioning
confidence: 67%
“…A significant upregulation of Hsp70 expression has been detected in CNS lesions from MS patients (63,64,68 (103). These data suggest that Hsp70 upregulation may increase susceptibility to autoimmune demyelinating disease.…”
Section: Cellular Responsementioning
confidence: 67%
“…These results are partially consistent with previous studies performed by Mycko and colleagues, in which all animals developed clinical signs of the disease but the Hsp70.1 KO mice developed a milder form of EAE. Furthermore, these authors also demonstrated that the passive transference of Hsp70.1-deficient lymphocytes with either MOG antigen- or polyclonal restimulation did not induce EAE in C57BL/6 WT mice [38].…”
Section: Discussionmentioning
confidence: 92%
“…Also Hsp70 has been shown to enhance autoimmunity in EAE. Particularly, our group has found that mice deficient in Hsp70 display almost complete resistance to EAE (Mycko et al, 2008). Hsp70 deficiency was associated in this study both with dysfunction in the activation of autoreactive T cells by antigen presenting cells and with increased susceptibility of T cells to apoptosis (Mycko et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Since both Notch and Hsp70 have been previously found to be critically involved in the generation of autoimmune demyelination (Aquino et al, 1997;Cwiklinska et al, 2010Cwiklinska et al, , 2003Elyaman et al, 2007;Jurynczyk et al, 2008Jurynczyk et al, , 2005Lund et al, 2006;Minter et al, 2005;Mycko et al, 2008Mycko et al, , 2004Reynolds et al, 2011), we investigated interactions between NICD1 and Hsp70 in mice immunized with a myelin antigen MOG 35-55 . Using coimmunoprecipitation we detected complexes of Hsp70 and NICD1 in MOG 35-55 -reactive CD4…”
Section: Accepted Manuscriptmentioning
confidence: 99%